2017
DOI: 10.3390/met7090362
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Strain Aging Behaviour in AISI 316L Austenitic Stainless Steel under As-Received and As-Welded Conditions

Abstract: In the current study, dynamic strain ageing (DSA) phenomena in 316L austenitic stainless steel was investigated under as-received and as-welded conditions. A tensile test was carried out on as-received and as-welded samples for the temperatures of 25-800 • C at a strain rate of 1 × 10 −3 s −1 . Microstructure and fracture surfaces were investigated by optic and scanning electron microscopes (SEM). 316L austenitic stainless steel showed different DSA behavior under as-received and as-welded conditions, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…2). The results of this study are similar to those of Muhamed et al [20]. The authors investigated the DSA behaviour of 316L ASS and subjected the samples to a hot tensile test in the 25-800°C range.…”
Section: Resultssupporting
confidence: 88%
“…2). The results of this study are similar to those of Muhamed et al [20]. The authors investigated the DSA behaviour of 316L ASS and subjected the samples to a hot tensile test in the 25-800°C range.…”
Section: Resultssupporting
confidence: 88%
“…Consequently, its use in many industrial areas such as aerospace, defense, automotive, energy, and petrochemicals is increasing, depending on new research and innovations on alloy steels. 49…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that Mo dramatically reduces the carbon diffusion coefficient in ferrite 7,8 and slows down iron self-diffusion. 9,10 In complex alloy steels, the diffusion mobility of carbon can be two times lower than that in simple ferrite. It is clear that Mo avoids brittleness due to another mechanism besides its effect on carbide diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature studies have shown that the PLC effect occurs not only in copper, aluminum and nickel alloys [2][3][4]17,18], but also in some steel grades. Plastic instability phenomenon was observed in steels with increased Cr content [7,19], austenitic stainless steels [20], Hadfield steels [21] and dual phase (DP) steels [22]. Some of the AHSSs are also prone to plastic instability phenomenon, such as high-manganese Twinning-Induced Plasticity (TWIP) steels [8], medium-manganese steels [6,13] and Q&P steels [10].…”
Section: Introductionmentioning
confidence: 99%